Protocol for a case–control study investigating the clinical phenotypes and genetic regulation of endometriosis in Indian women: the ECGRI study - Shashank Shekhar; Gita Mishra; Grant Montgomery; Rahul K. Gajbhiye; Pranay Phukan; Kedar Padte; Pramathes DasMahapatra; Bimal M. John; Chaitanya Shembekar; Aishwarya V. Bhurke; Nilajkumar Bagde; Ketki Kulkarni; et al. (BMJ Open)
Introduction Endometriosis is one of the common, gynaecological disorders associated with chronic pelvic pain and subfertility affecting ~10% of reproductive age women. The clinical presentation, etiopathogenesis of endometriosis subtypes and associated risk factors are largely unknown. Genome-Wide Association (GWA) Studies (GWAS) provide strong evidence for the role of genetic risk factors contributing to endometriosis. However, no studies have investigated the association of the GWAS-identified single-nucleotide polymorphism (SNPs) with endometriosis risk in the Indian population; therefore, one-sixth of the world’s population is not represented in the global genome consortiums on endometriosis. The Endometriosis Clinical and Genetic Research in India (ECGRI) study aims to broaden our understanding of the clinical phenotypes and genetic risks associated with endometriosis.Methods and analysis ECGRI is a large-scale, multisite, case–control study of 2000 endometriosis cases and 2000 hospital controls to be recruited over 4 years at 15 collaborating study sites across India covering representative Indian population from east,north-east, north, central, west and southern geographical zones of India. We will use the World Endometriosis Research Foundation Endometriosis Phenome and Biobanking Harmonisation Project (WERF-EPHect) data collection instruments for capturing information on clinical, epidemiological, lifestyle, environmental and surgical factors. WERF-EPHect standard operating procedures will be followed for the collection, processing and storage of biological samples. The principal analyses will be for main outcome measures of the incidence of endometriosis, disease subtypes and disease severity determined from the clinical data. This will be followed by GWAS within and across ethnic groups.Ethics and dissemination The study is approved by the Institutional Ethics Committee of Indian Council of Medical Research-National Institute for Research in Reproductive Health and all participating study sites. The study is also approved by the Health Ministry Screening Committee of the Government of India. The results from this study will be actively disseminated through discussions with endometriosis patient groups, conference presentations and published manuscripts.